Interferon-gamma release assay for screening of tuberculosis infection in children - Huiwen Zheng; Jing Xiao; Feina Li; Hao Chen; Deze Li; Yonghong Wang; Yajie Guo; Yuying Chen; Chen Shen (BMC Infectious Diseases, 2023)
Abstract Background Interferon-gamma release assay (IGRA) is the main tool for the diagnosis of latent tuberculosis (TB) infection (LTBI). However, the indeterminate results were more frequent in children, and the underlying reasons were largely speculative. We aimed to compare QuantiFERON-TB Gold In-Tube (QFT-GIT) with X.DOT-TB (XDOT) for diagnosing LTBI, and to identify the risk factors associated with indeterminate results in children. Methods A retrospective study for children<18 years old, at risk for LTBI or progression to TB disease, received either QFT-GIT or X.DOT-TB tests was performed at Beijing Children’s Hospital from August 2019 to August 2022. Results A total of 33,662 children were recruited, including 15,129 (44.9%) tested with X.DOT-TB and 18,533 (55.1%) with QFT-GIT. Proportion of positive and indeterminate results in children with respiratory disease was significantly higher than did that with other diseases, respectively (P < 0.001). The indeterminate rate of X.DOT-TB and QFT-GIT results decreased with increasing age (P < 0.001). Proportion of QFT-GIT indeterminate results was higher than that of X.DOT-TB across age groups. Male, age and disease classification all presented a statistically significant association with indeterminate IGRA results. Conclusions The positive rates of X.DOT-TB and QFT-GIT in children were 3.1% and 1.8%, respectively. The X.DOT-TB assay performed better than QFT-GIT in children, and male, age and underlying diseases were associated with an increased risk of indeterminate IGRA results.